Students’ Perception on Writing Weekly Journal at English Education Department of Universitas Muhammadiyah Yogyakarta - Esih Karlinawati (PBI 15 UMY 050, 2015)
*50 The researcher found that there were still a lot of problems in academic writing at English Education Department (EED) of Universitas Muhammadiyah Yogyakarta (UMY). Students had less idea, and they got unclear feedback from the lecturer on their writing, so those problems made them confused how to write. Whereas, writing weekly journal was a new mode of learning in seventh semester, so this research investigated student’s perception and identified student’s obstacles that students found in the implementation of writing weekly journal at EED of UMY. The data for the research were collected through descriptive qualitative design. The participants who were interviewed were three students of batch 2011 from three different groups who did the writing weekly journal in academic year of 2014/2015. The first result of the research about the students’ perception of writing weekly journal reported that it improved students’ skill in reading, writing, and speaking. Besides, it enhanced students’ vocabularies and knowledge. However, this activity could become monotonous activity since they did hand writing in the whole semester, but the students argued that writing weekly journal should be continued as the learning method. The second result of the research showed that the personal obstacles from students which they faced in doing this activity, namely: students thought that (1) the article was too long, (2) it had advanced level of words, (3) students got no reading habit, (4) students got less idea toward the topic of articles, (5) they got lack of vocabularies, (6) The article topic was unfamiliar for the students. In addition, the vi research revealed that another student obstacle come from the lecturer which was giving unclear feedback. Last, there were some recommendations based on the participants’ view to face the obstacles of writing weekly journal activity. Students should have reading habit, improved vocabularies, discussed with their friends about the article, and made a brain storming before the writing weekly journal began. Students also suggested that the lecturer should give clear feedback.